(3GdeQhAI heG LGA aj Pdc Yf GdfHj Udi Gddg Ydjg hSde hYf GdUMGHIs - (3GdeMhdj, CHh HcQ, GHf GdeQRHGf, eMnqeO Hf Nda Hf GdeQRHGf Hf HSGe, J (B309 (3g`s ((3YeQ Hf Ydjs)
(3ChdgG (B:s
(3HSe Gddg (B... (3bjd dg GNHQc GdTjN (B.. (3CHj GdbGSe GdMSf Hf (B... (3GdCfUGQj YQa HGHf GdbWGf bQCg Ydjg hCfG CSeY (B... (3Yf GdfHj Udi Gddg Ydjg hSde (B" (3cQe GdeQA JbhGg heQhAJg Ybdg (B" ...s
(3BNQgG (B:s
... (3bhd eQI Hf agO Hf TjHGf Mjf jbhd (B: (3pEnqf GdpqSnjGnOnI nhGrdoeoQhnAnI pYrdkbG nMrjoK GdpqSneGoc penf GdpqSneGpc GrdnCrYnRod nhpEnPG nJnfGnanQ nSpqjnOGpf pHoerYpLmR nWnQnMG GrdpbnOGnM nanZGnQ perfngG GdnCrenKod (B... (3nhncnPG GrdoeoQhnAoI nerf nJnYnqdnb nMs
(3Yf fSNI HNW GdMGaX GdQMHjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 \115s
(3UdI GdNda HehUhd GdSda deMeO Hf WGgQ GdQhOGfj GdShSj (B/ 404s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdMOjK hGdeUWdMs